Reactions of Sulfonium Salts with 2,3-Dioxopyrrolidine Derivatives: A Concise Synthesis of Spirocyclopropane - Zhang, Shuang; Hu, Xiu-Qin; Wang, Zhu-Yin; Xu, Peng-Fei (Synthesis, 2015)
An efficient base-promoted spirocyclopropanation of 2,3-dioxopyrrolidine derivatives with sulfonium salts is described. This reaction enables a novel concise access to polysubstituted spirocyclopropane derivatives in good yields and with a trans/cis ratio of up to >20:1 under mild conditions.
Keywords: spiro compounds; spirocyclopropane; sulfur ylides; sulfonium salt; 2,3-dioxopyrrolidine; heterocycles